Screening pearl millet genotypes for resistance to Striga hermonthica and compatibility to Fusarium oxysporum f.sp. strigae - Rouamba, Armel; Hussein Shimelis; Drabo, Inoussa; Mrema, Emmanuel; Gangashetty, Prakash Irappa (Elsevier, 2024)
Pearl millet (Pennisetum glaucum [L.] R. Br., 2n = 2x = 14) is a nutritionally rich and climate-resilient food crop cultivated globally. It is a crucial staple crop in Burkina Faso and the dry Sahel region, encompassing Niger, Mali, and Senegal. However, the yield of pearl millet is relatively low in the region (<0.85 tons ha−1) due to Striga hermonthica (Sh) infestation, bird damage, insect pests, diseases, and low-yielding open-pollinated landrace varieties. The study aimed to screen genetically diverse pearl millet accessions for Sh resistance and compatibility to a Striga bio-control agent, Fusarium oxysporum f. sp. Strigae (FOS), to select contrasting and promising parents for resistance breeding and production. One hundred and fifty genotypes were evaluated in Sh hotspot fields in the rain-fed and greenhouse conditions using an alpha lattice design and two replications in Burkina Faso. Significant differences were recorded among the tested pearl millet genotypes for the assessed agro-morphological and Striga resistance. Days to flowering was significantly delayed in the assessed genotypes due to Sh infestation. Applying FOS on pearl millet seed significantly reduced the mean Striga number in Sh-infested conditions. The following genotypes: IP-3098, IP-6112, IP-9242, IP-10579, and IP-11358 were identified as exhibiting Sh resistance and were compatible to FOS. The pearl millet genotypes supported few to none Sh emerged plants with comparatively low values under the Striga number progress curve. The selected genotypes are useful parents to breed for Striga resistance and integrated management in Burkina Faso and related agroecologies.